Effect of pre and post badminton match on shoulder rotators strength and range of motion in recreational badminton players - Adapurv, Virupakshagouda V.; Pinto, Royline Fathima; K. P., Rajeetha (International Journal of Research in Medical Sciences, 2025)
Background: Badminton is recognized as the fastest racquet sport, with shuttle speeds during match play ranging from 50–75 m/s and post-smash velocities exceeding 100 m/s. Singles competition demands high levels of fitness, while doubles require sustained aggression and rapid reflexes. Players rely on aerobic endurance, agility, strength, speed, and precision. The biomechanics of badminton involve six rapid motion phases, with acceleration lasting just 0.05 seconds being the most injury-prone. Identifying early signs of shoulder dysfunction is essential to prevent long-term damage. This study aims to evaluate the effect of a single badminton match on shoulder rotator strength and range of motion (ROM) in recreational male players. Methods: A total of 44 recreational male badminton players participated in the study. Shoulder rotator strength and ROM were assessed both before and after match play. Strength was measured using a handheld dynamometer, and ROM was evaluated using a goniometer. A p value of <0.01 was considered statistically significant. Results: Post-match analysis revealed a significant decrease in internal rotator ROM and strength, alongside an increase in external rotator ROM. External rotator strength also showed a notable reduction. These changes were statistically significant (p<0.001), indicating acute biomechanical alterations following match play. Unpaired t-test analysis revealed statistically significant differences in shoulder internal and external rotation ROM (p<0.001), internal rotator strength (p<0.001) and external rotator strength (p<0.05) between pre- and post-match assessments. Conclusion: Post-match findings indicated a decrease in shoulder internal rotation ROM and external rotator strength, alongside an increase in external rotation ROM and internal rotator strength. These changes highlight the acute impact of match play on shoulder function and underscore the need for targeted conditioning and recovery strategies.